Evaluation of serum calprotectin levels in patients with polycystic ovary syndrome - Rıfat Şener; Süleyman Erkan Alataş; Ömer Tolga Güler (Scientific Reports)
Abstract Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women of reproductive age. PCOS is associated with many chronic complications such as endometrial thickening, endometrial cancer, breast cancer, infertility, dyslipidemia, and long-term cardiovascular disease. Therefore, many parameters and markers should be used in the evaluation of patients diagnosed with PCOS. Calprotectin has also been shown to be an important marker of destruction in many diseases that progress with inflammatory processes. The objective of our study was to examine the diagnostic efficacy of calprotectin in the context of polycystic ovary syndrome. In this study, 39 patients diagnosed with polycystic ovary syndrome and 41 healthy controls were analyzed. Serum calprotectin levels were compared between patients with different phenotypes of PCOS and a control group. Our study demonstrates significant differences in hormonal and inflammatory parameters between PCOS patients and healthy controls. PCOS patients exhibited significantly lower FSH levels and higher LH levels, resulting in a marked increase in the LH/FSH ratio. Additionally, DHEA-S and total testosterone levels were significantly elevated in the PCOS group, while SHBG levels were notably lower. The free androgen index (FAI) and serum calprotectin levels were also significantly higher in the PCOS group, highlighting the potential role of calprotectin in the pathophysiology of the disorder. Our study demonstrated that serum calprotectin levels are significantly higher in patients with PCOS compared to healthy controls. This finding underscores the potential role of calprotectin in the pathophysiology of PCOS and suggests that this marker could provide valuable insights into the inflammatory processes associated with the condition. However, further large-scale and long-term studies are necessary to better understand the impact of calprotectin on different PCOS phenotypes and its potential application in clinical practice.